Harrison's pulmonary and critical care medicine - Loscalzo, Joseph; Harrison, Tinsley Randolph 1900-1978 (McGraw-Hill Medical, 2013)
Featuring a superb collection of chapters on pulmonary and critical care medicine from Harrison's Principles of Internal Medicine, Eighteenth Edition and the acclaimed companion DVD, this concise clinical companion also includes updates and new developments, and board review questions. It is ideal for the classroom, wards, or exam/certification preparation. Features: full-color presentation; content derived from Harrison's, the world's leading and most trusted medical text; convenient, carry-anywhere presentation.